Cellular internalization effect of Ara27 in various cell lines - Minseo Kim; Sangkyu Park; Jeongmin Seo; Sangho Roh (Journal of Animal Reproduction and Biotechnology, 2022)
Protein and peptide candidates are screened to apply therapeutic application as a drug. Ensuring that these candidates are delivered and maximized effectiveness is still challenging and a variety of studies are ongoing. As drug delivery system vehicles, cell-penetrating peptide (CPP) can deliver various kinds of cargo into the cell cytosol. In a previous study, we developed Ara27 CPP, which are a zinc knuckle family protein of Arabidopsis, and confirmed internalization in human dermal fibroblasts and human dental pulp stem cells at low concentration with short time treatment condition without any toxicity. Ara27, an amphipathic CPP, could be modified and utilized in the biomedical field excluding the risk of toxicity. Therefore, we would like to confirm the non-toxic induced penetrating ability of Ara27 in various cell lines. The purpose of this study was to screen the cell internalization ability of Ara27 in various cell lines and to confirm Ara27 as a promising core CPP structure. First, Ara27 was screened to confirm non-toxicity concentration. Then, fluorescence-labeled Ara27 was treated on human normal cell lines, cancer cell lines and animal cell lines to identify the cellular internalization of Ara27. Ara27 was well intracellular localized in all cell lines and the intensity of fluorescence was remarkably increased in time pass manner. These results indicate that Ara27 has the potential as a core structure for applications in various drug delivery systems.